Opioid-Sparing Cardiac Anesthesia: Secondary Analysis of an Enhanced Recovery Program for Cardiac Surgery. (December 2020) - Grant, Michael C.; Isada, Tetsuro; Ruzankin, Pavel; Gottschalk, Allan; Whitman, Glenn; Lawton, Jennifer S.; Dodd-o, Jeffrey; Barodka, Viachaslau
Abstract : BACKGROUND: Cardiac anesthetics rely heavily on opioids, with the standard patient receiving between 70 and 105 morphine sulfate equivalents (MSE; 10–15 µg/kg of fentanyl). A central tenet of Enhanced Recovery Programs (ERP) is the use of multimodal analgesia. This study was performed to assess the association between nonopioid interventions employed as part of an ERP for cardiac surgery and intraoperative opioid administration. METHODS: This study represents a post hoc secondary analysis of data obtained from an institutional ERP for cardiac surgery. Consecutive patients undergoing cardiac surgery received 5 nonopioid interventions, including preoperative gabapentin and acetaminophen, intraoperative dexmedetomidine and ketamine infusions, and regional analgesia via serratus anterior plane block. The primary objective, the association between intraoperative opioid administration and the number of interventions provided, was assessed via a linear mixed-effects regression model. To assess the association between intraoperative opioid administration and postoperative outcomes, patients were stratified into high (>50 MSE) and low (⩽50 MSE) opioids, 1:1 propensity matched based on 15 patients and procedure covariables and assessed for associations with postoperative outcomes of interest. To investigate the impact of further opioid restriction, ultralow (⩽25 MSE) opioid participants were then identified, 1:3 propensity matched to high opioid patients, and similarly compared. RESULTS: A total of 451 patients were included in the overall analysis. Analysis of the primary objective revealed that intraoperative opioid administration was inversely related to the number of interventions employed (estimated −7.96 MSE per intervention, 95% confidence interval [CI], −9.82 to −6.10, P < .001). No differences were detected between low (n = 136) and high (n = 136) opioid patients in postoperative complications, postoperative pain scores, time to extubation, or length of stay. No differences were found in outcomes between ultralow (n = 63) and high (n = 132) opioid participants. CONCLUSIONS: Nonopioid interventions employed as part of an ERP for cardiac surgery were associated with a reduction of intraoperative opioid administration. Low and ultralow opioid use was not associated with significant differences in postoperative outcomes. These findings are hypothesis-generating, and future prospective studies are necessary to establish the role of opioid-sparing strategies in the setting of cardiac surgery.